Leiomyomatosis Peritonealis Disseminata Following Laparoscopic Surgery With Uncontained Morcellation: 13 Cases From One Institution - Chen, Xin; Liu, Haiyuan; Shi, Honghui; Fan, Qingbo; Sun, Dawei; Lang, Jinghe (Frontiers in Surgery, 2021)
Objectives: To investigate the clinical characteristics, treatment and prognosis of leiomyomatosis peritonealis disseminata (LPD) following laparoscopic surgery with uncontained morcellation and to summarize clinical features of iatrogenic LPD based on published literature together with our own experience. Methods: A cohort of 13 cases with iatrogenic LPD diagnosed and treated in Peking Union Medical College Hospital from 2011 to 2020 was reported focusing on clinical characteristics, treatment and prognosis. Results: All the patients had a history of laparoscopic myomectomy with uncontained morcellation. The average age was 35.6 (range 25-47) years. The interval between initial laparoscopic surgery and first diagnosis of LPD was 6.08 years on average (range 1-12). Most of the patients had no obvious symptoms.The accuracy of preoperative diagnosis was low. Two patients had been treated with gonadotropin-releasing hormone agonist (GnRH-a) before surgery without obvious effect. The nodules of LPD are usually located in the lower half of the peritoneal cavity. The most commonly involved site was the pouch of Douglas. The number of nodules ranged from 3 to over 10, and they ranged in size ranged from 0.3 to 22 cm. All patients underwent surgical treatment: six patients underwent laparoscopy and seven underwent laparotomy. Pathology results confirmed LPD. The immunohistochemical profile indicated LPD tends to be positive strongly for desmin, caldesmon, ER, PR and SMA. Only one patient underwent post-operative treatment with GnRH-a. All patients were followed for an average period of 49 months without recurrence. Conclusion: Iatrogenic LPD is a relatively rare condition. Patients usually exhibit no hormonal stimulation factors. Surgery is the main method of treatment, and hormone suppressive therapy is only rarely used. The nodules are usually large and less numerous, and most involve the pelvis. The prognosis of iatrogenic LPD seems good.